(untitled) (Research, Society and Development, 2025)
This study aimed to evaluate the impact of different mechanical finishing and polishing techniques on the surface roughness of microwave-polymerized thermally activated acrylic resin (TAAC) samples. For this purpose, 50 samples were prepared in TAAC polymerized by microwave energy and distributed into 5 groups according to the finishing and polishing protocol (n = 10): GC (no treatment), G1 (only drills), G2 (drills and lathe), G3 (drills, sandpaper and lathe) and G4 (drills, rubber and lathe). The surface roughness evaluation was performed by the average of five readings on a portable roughness meter with a measurement path configured with an excursion of 0.25 µm and a speed of 0.5 mm/s. The mean surface roughness values ​​for each group were tabulated and statistically analyzed using the nonparametric Mann-Whitney Rank Sum Test (comparison between experimental and control groups) and Kruskal-Wallis (comparison between experimental groups), with a 95% confidence interval. The surface roughness results show that there was a statistically significant difference between the GC and the other experimental groups (P<0.001). Among the experimental groups, there was a statistically significant difference between group G1 (1.34 Ra) and the other groups (p = 005151). However, there was no statistically significant difference between groups G2 (1.45 Ra), G3 (1.45 Ra) and G4 (1.45 Ra). It was concluded that finishing the surface of the RAAT with drills associated with polishing with sandpaper, rubber and lathe results in smoother surfaces with less potential for biofilm accumulation.